Quality of life improves during antiviral therapy with bulevirtide - Eichholz, Julia Carolin; Dietz-Fricke, Christopher; Mrowietz, Simon Kristian; Dinkelborg, Katja; Port, Kerstin; Wedemeyer, Heiner; Deterding, Katja (Zeitschrift für Gastroenterologie, 2025)
Hepatitis D virus (HDV) infection is the most severe form of viral hepatitis and has been shown to be associated with reduced quality of life. With the approval of the entry inhibitor bulevirtide, the first specific agent for HDV infection became available. Here, we report data on quality of life (QOL) before and during antiviral therapy with bulevirtide in a single center real-world cohort.We investigated QOL assessed by the Short Form 36 Health Survey (SF-36) in 25 patients undergoing antiviral treatment with bulevirtide. Surveys were completed before the beginning of antiviral therapy and up to week 152 of treatment as a long-term follow up.The study cohort included 7 women (28%) and 18 men (72%) with a median age of 46 years. Liver cirrhosis (defined as liver stiffness measurement ≥ 15.2 kPa) was present in 16 patients (64%) at the start of antiviral treatment. During the course of antiviral treatment with bulevirtide, scores for vitality, mental health and bodily pain significantly improved. The physical component score showed a minimal clinically important increase of ≥ 2.5 points in 10 patients (42%) at week 24 and in 6 patients (30% of patients with full data available) at week 48. The mental component score showed a minimal clinically important increase (≥ 2.5 points compared to baseline) in 10 patients (42%) at week 24 and in 12 patients (60%) at week 48. In the patient cohort with an improvement of physical or mental component scores at week 48, a further improvement beyond week 48 was evident in single cases but not in all patients. Importantly, changes of physical or mental component scores were not associated with virological or biochemical responses.Vitality, mental health and bodily pain improved during BLV treatment. As a sign of the good tolerability of BLV, no significant deteriorations in QOL scores were observed. Findings need to be confirmed and further evaluated in larger cohorts and longer follow-up is needed.
Keywords: hepatitis D; bulevirtide; quality of life; SF-36